RADI-37. CLINICAL RISK FACTORS FOR INTRACRANIAL HEMORRHAGE OF SOLID MELANOMA BRAIN METASTASES AFTER RADIOSURGERY. (12th August 2019) - Okoukoni, Catherine; LeCompte, Michael; Hughes, Ryan; McTyre, Emory; Cramer, Christina; Whitlow, Christopher; Chan, Michael
Abstract: PURPOSE: Melanoma brain metastases (MBM) are among the most common solid tumors associated with intracranial hemorrhage (ICH). Our objective is to investigate risk factors for post-radiosurgery intracranial hemorrhage (PRH). METHODS: We collected demographic, clinical, treatment, toxicity, survival, and imaging data for patients with solid MBM who underwent SRS between 2000 and 2016 at our institution. Bleed free survival (BFS) and overall survival (OS) analyses were performed using Kaplan–Meier methods. Logistic regression was used to identify PRH risk factors. RESULTS: From 2000 to 2016, 107 patients with a total of 548 solid MBM received SRS. Median patient age at time of SRS was 63.2 years. Median MBM volume was 2.8 cm 3 (range 0.01–21.3 cm 3 ). MBM were in the cortex (n = 431), cerebellum (n= 85), basal ganglia (n= 23), and brain stem (n= 9). MBM were treated to a median dose of 20 Gy (range 14–20 Gy). Seventeen patients received immunotherapy (IT) within 1 year of SRS, 7 patients received concurrent immunotherapy (XR-IT). Median follow-up and OS was 13.5 months and 10.8 months, respectively. Median BFS was 8.3 months. PRH occurred in 123 MBM (22%). MBM volume (p= 0.0001), total MBM volume (p= 0.0006), IT (p= 0.04), and XR-IT (p= 0.03) were associated with increased PRH. PRH cumulative incidence within 24 mo of SRS was increased in MBM > 2.8 cm 3 compared with patients with smaller MBM: 27.5% verse 5.3%, respectively. Age, sex, hypertension, MBM location, total MBM number, and marginal dose (p > 0.05) did not significantly impact risk of PRH. No significant difference in 6, 12, or 24 mo actuarial OS rates were observed in patients with PRH (p > 0.05). CONCLUSIONS: Patients with larger MBM volume and IT within 1 year of SRS have the greatest risk of PRH. PRH did not significantly impact OS in this study.